Impelemntasi E-Monitoring Perjalanan Dinas Badan Pusat Statistik (Bps) Kabupaten Kotawaringin Timur Berbasis Web - Susi Santya; Minarni Minarni (IKRAITH-Teknologi, 2022)
Official travel is a trip made by an employee or employee in a company or agencywith official duties. Each company or agency has different procedures in preparingfor business travel needs. One of the agencies that carry out official trips is theCentral Statistics Agency (BPS) of East Kotawaringin Regency. Official trips at theCentral Statistics Agency (BPS) of East Kotawaringin Regency were carried outdue to the scheduled monthly or annual agenda as well as external invitationsrelated to the Central Statistics Agency (BPS) of East Kotawaringin Regency.Employees who will go on business trips will be appointed directly by the Head ofBPS Kotawaringin Timur Regency in accordance with their respective fields. Tocarry out official trips, each employee needs a cover letter or commonly called aLetter of Assignment for business trips within the city and an Official Travel Letter(SPD) for business trips out of town. Correspondence is done using Microsoft Wordand Microsoft Excel. The manufacturing procedure cannot be done quickly becauseit has to enter and edit employee data one by one so it takes quite a long time. Withthese problems, the process of making correspondence and its management is stillnot systematic. So that the Central Statistics Agency (BPS) of East KotawaringinRegency is experiencing problems due to the slow procedure for making officialtravel correspondence, data management of official travel reports, and the Head ofthe Central Statistics Agency (BPS) of East Kotawaringin Regency cannot controlor monitor employees who are traveling. remote service. Therefore, it is necessaryto have an information system that can facilitate data management and supervisionof official travel at the Central Statistics Agency (BPS) of East KotawaringinRegency. This information system is implemented in the form of a web-basedOfficial Travel E-Monitoring that can help the performance of the Central StatisticsAgency (BPS) of East Kotawaringin Regency to minimize the procedure for makingcorrespondence so that it is faster, easier, automatic and organized.